2019
DOI: 10.1186/s12876-019-1108-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prevalence and risk factors of helicobacter pylori infection in an oilfield Community in Hebei, China

Abstract: BackgroundOnly a paucity of large-scale perspective and cross-sectional studies on H. pylori infection in China have been published. The purpose of this study was to investigate the prevalence and risk factors for H. pylori infection among residents of Jidong community located in Hebei Province of China.MethodsA perspective, cross-sectional study was conducted in Jidong community. Questionnaires and 13C-urea breath test were performed, and 10-ml blood samples were obtained for laboratory tests.ResultsFour thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 27 publications
3
33
4
1
Order By: Relevance
“…These findings support the hypothesis that moderate alcohol consumption may facilitate spontaneous elimination of H. pylori infection in adults. 18 On the contrary, Wang et al 19 suggested that patients who consumed alcohol had a higher prevalence of active H. pylori infection than non-drinkers (OR: 1.139; 95% CI: 1.025-1.290; P ¼ 0.0407). Zhang et al 20 reported that in patients with functional dyspepsia, there is no significant association between active H. pylori infection and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the hypothesis that moderate alcohol consumption may facilitate spontaneous elimination of H. pylori infection in adults. 18 On the contrary, Wang et al 19 suggested that patients who consumed alcohol had a higher prevalence of active H. pylori infection than non-drinkers (OR: 1.139; 95% CI: 1.025-1.290; P ¼ 0.0407). Zhang et al 20 reported that in patients with functional dyspepsia, there is no significant association between active H. pylori infection and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to those in European countries, which are around 60 years old [ 25 ]. It has been reported that the prevalence of H. pylori infection increased by age manner [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The infection was found more frequently in married subjects than singles ( P = .02), those with a lower education level ( P = .01), using barreled vs. piped water ( P = .04), and more frequently consuming garlic ( P = .03) as well as in alcohol consumers when compared to non‐drinkers ( P = .02). Furthermore, responders that were familiar with the route of H pylori transmission and related diseases had a lower prevalence of the infection than those who were not aware ( P = .01, P = .03, respectively) 7 …”
Section: Helicobacter Pylori Prevalence Worldwidementioning
confidence: 95%
“…A prospective, cross‐sectional study HIOC ( Helicobacter pylori Infection in Oilfield Community) involving employees and their family members was conducted in the Jidong community of Hebei province, China 7 . Among the 4796 consecutive study subjects tested by UBT, H pylori infection was present in 52.3%.…”
Section: Helicobacter Pylori Prevalence Worldwidementioning
confidence: 99%